Towards an Observation of Active Conformations in Asymmetric Catalysis: Interaction‐Induced Conformational Preferences of a Chiral Thiourea Model Compound. Issue 35 (26th July 2016) - Kreienborg, Nora M.; Pollok, Corina H.; Merten, Christian
Abstract: The observation of the active species is the goal of most spectroscopic investigations on enantioselective organocatalysts in solution. Although NMR spectroscopy is widely applied, it has low sensitivity for conformational changes or the chiral nature of the interactions. In the present work, we exemplify the use of vibrational circular dichroism (VCD) spectroscopy for the characterization of a chiral thiourea model compound in nonpolar and polar solvents, as well as for a detailed analysis of its interaction with a model reactant. We discuss solvent‐induced conformational changes of the thiourea, and provide evidence for an unexpected binding topology between the thiourea and an acetate anion. The results clearly showcase the possibilities offered by using VCD spectroscopy in the characterization of chiral organocatalysts. Abstract : Good vibrations : Using vibrational circular dichroism (VCD) spectroscopy, the conformational preferences of a chiral thiourea in different solvents and its interaction with an acetate anion were investigated. Characteristic spectral signatures were found for different groups of conformers and showcase the potential of using VCD spectroscopy for studying reactant–catalyst interactions (see scheme).